Response Surface Design for Optimization of Microcystis aeruginosa Removal by Ultrasonic Irradiation - Fan1, Gongduan; Lin1, Qian; Luo2, Jing; Chen3, Jieyun; Chen1, Liru; Lin1, Rujing (Asian Journal of Chemistry, 2014)
Major bloom-forming organism is the species Microcystis aeruginosa which produces hepatotoxin microcystin into water and it is harm to aquatic organisms and humans. Ultrasound is an environment-friendly technology and inhibits the growth of algae effectively. First of all, the effect of ultrasonic frequency, power density and irradiation time on Microcystis aeruginosa through single factor experiments was studied. Then the optimized values of the three parameters were determined by Box-Behnken model of response surface design. Results showed that the removal efficiency of chlorophyll-a reached to (99.33 ± 0.02) % after sonication for 24 s at 580 kHz and 0.089 W/mL. Ultrasonic technology can remove Microcystis aeruginosa in water effectively.